2020
DOI: 10.3390/ani10010171
|View full text |Cite
|
Sign up to set email alerts
|

β-Sitosterol Attenuates High Grain Diet-Induced Inflammatory Stress and Modifies Rumen Fermentation and Microbiota in Sheep

Abstract: β-sitosterol (BSS) is a plant-derived natural bioactive compound, its cellular mechanism of anti-inflammatory activity has been proven recently. Little information is available regarding the application of BSS on ruminants under high grain diet. The objective of this study was to evaluate the effects of dietary BSS supplementation on inflammatory response, ruminal fermentation characteristics and the composition of the ruminal bacterial community under high grain diet. Eight rumen-cannulated Hu sheep (59.7 ± 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 43 publications
(48 reference statements)
4
16
0
Order By: Relevance
“…The higher levels of ARE supplementation (5% and 8% dry matter) in this study increased the abundance of Rikenellaceae _RC9_gut_group, Succiniclasticum and Prevotella _1 when compared with control calves, which indicated that ARE contributed to the growth of protein and carbohydrate degrading rumen microbes, and to the supply of energy for yak calves. Studies have demonstrated that Prevotella _1 contributed to the production of rumen acetic acid and propionate acid, 58,61 which is consistent with the higher rumen acetic acid propionic acid concentrations in the ARE 80 than ARE 0 group in the current results. In addition, supplementary ARE increased the proportion of the Ruminococcaceae _NK4A214_group and Christensenellaceae _R‐7_group.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The higher levels of ARE supplementation (5% and 8% dry matter) in this study increased the abundance of Rikenellaceae _RC9_gut_group, Succiniclasticum and Prevotella _1 when compared with control calves, which indicated that ARE contributed to the growth of protein and carbohydrate degrading rumen microbes, and to the supply of energy for yak calves. Studies have demonstrated that Prevotella _1 contributed to the production of rumen acetic acid and propionate acid, 58,61 which is consistent with the higher rumen acetic acid propionic acid concentrations in the ARE 80 than ARE 0 group in the current results. In addition, supplementary ARE increased the proportion of the Ruminococcaceae _NK4A214_group and Christensenellaceae _R‐7_group.…”
Section: Discussionsupporting
confidence: 90%
“…The core bacterial genus Rikenellaceae _RC9_gut_group is classified in the Rikenellaceae family, which has been reported to alleviate oxidative stress by suppressing proinflammatory cytokines in inflammatory tissues, 58 and to be involved in the degradation of structural carbohydrates 59 . Succiniclasticum converts succinate into propionate, an important precursor of glucose in ruminants 60 .…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, the decreased Shuttleworthia observed with the BSG hydrolysates and ANT treatments may explain the decreased starch digestibility with FlaH and ANT. A recent study has shown a negative correlation between Shuttleworthia and lactate and NH 3 -N concentration [ 64 ], thus explaining the higher NH 3 -N production with BSG hydrolysates.…”
Section: Resultsmentioning
confidence: 99%
“…During the past decades, the regulatory roles of gut microbiota on various diseases, including PCOS, have gained increasing attention ( 44 , 45 ). β-sitosterol could improve rumen fermentation in sheep by reducing microbial community and metabolic disorders induced by high grain feed ( 46 ). Therefore, we have reason to suspect that the protective effect of β-sitosterol on PCOS may be related to gut microbiota.…”
Section: Discussionmentioning
confidence: 99%